Aplikasi Penjadwalan Pertandingan Basket pada StiFest menggunakan Metode Round Robin - Nandesha Nensia Dwi Cristanti; Pantjawati Sudarmaningtyas; Erwin Sutomo (Jurnal Sistem Informasi Universitas Dinamika, 2016)
Basketball game in this StiFest activity has many fans who sign up and is steadily increasing. The game system is used based on the number of teams that register. Scheduling basketball game on StiFest use system Knock Out game (autumn) and a half of competition / group. Scheduling current game, done manually at random by the committee. In this way, it is feared foul play by the committee to provide an easy match for a particular team.Based from the issues, then made one basketball scheduling matches application using Round robin method. Round robin exact used to basketball scheduling matches application analyze based on half competition system because work based by time (quantum) which determined with every m